1994
DOI: 10.1103/physrevb.49.9746
|View full text |Cite
|
Sign up to set email alerts
|

Consistent low-energy reduction of the three-band model for copper oxides with O-O hopping to the effectivet-Jmodel

Abstract: A full three-band model for the CuO& plane with inclusion of all essential interactions -Cu-0 and 0-0 hopping, repulsion at the copper and oxygen and between themis considered. A general procedure of the low-energy reduction of the primary Hamiltonian to the Hamiltonian of the generalized t-t -J model is developed. An important role of the direct 0-0 hopping is discussed. Parameters of the effective low-energy model (the hopping integral, the band position, and the superexchange constant J) are calculated. An … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 24 publications
0
68
0
Order By: Relevance
“…This suggests that the dispersion should somehow be related to an effective nnn hopping which must be present even when t ′ = 0. While this effective long-range hopping is not explicitly present in the Hubbard model when t ′ = 0, it does appear in a t/U expansion to lowest order [47][48][49][50] as the so-called 3-site term, see Fig. 3(a) and Refs.…”
Section: The 2d Hubbard Model Hamiltonian H H Ismentioning
confidence: 99%
“…This suggests that the dispersion should somehow be related to an effective nnn hopping which must be present even when t ′ = 0. While this effective long-range hopping is not explicitly present in the Hubbard model when t ′ = 0, it does appear in a t/U expansion to lowest order [47][48][49][50] as the so-called 3-site term, see Fig. 3(a) and Refs.…”
Section: The 2d Hubbard Model Hamiltonian H H Ismentioning
confidence: 99%
“…However, the cuprate plane has long been known to be very poorly described by lowest-order perturbative approaches, and this has led to detailed efforts to derive more accurate low-energy descriptions from d-p [36] or three-band [37] models for the Cu and O orbitals. For clarity, we follow the systematic extension of the lowest-order analysis [30], where the direct in-plane O-O hopping, described by the overlap integral t pp , contributes to J through many possible fifth-and sixthorder processes.…”
Section: A Estimation Of Superexchange Parametersmentioning
confidence: 99%
“…In the study of the electronic structure of cuprates, correlation effects have been almost exclusively treated in the framework of model Hamiltonians. 16,46,47 Our estimation of the importance of electronic correlation contribution to J is obtained from the exact nonrelativistic Hamiltonian and, therefore, without making reference to the importance of any term entering into the definition of the electronic Hamiltonian. In the present work, the terms explicitly considered are, of course, those already defined in Anderson's original work.…”
Section: -29mentioning
confidence: 99%
“…A detailed study of the three-band model in the ''realistic'' region of the parameters has been reported recently. 16 In both, single-band and three-band models, perturbation theory is often used to obtain the magnetic coupling constant. In the first case, and up to second order, one obtains the Jϭ4t 2 /U expression corresponding to the original Anderson superexchange theory.…”
Section: Introductionmentioning
confidence: 99%